Herbert J. Izzo, Tuscan and Etruscan. The problem of linguistic substratum influence in central Italy. University of Toronto Press, Toronto-Buffalo, 1972; vi + 238 pp. (University of Toronto Romance Series, 20). - Williamson, Rodney (El Colegio de México, 1974)
Se reseñó el libro: Tuscan and Etruscan. The problem of linguistic substratum influence in central Italy.